Stereoselective synthesis of the polyketide chain of nagahamide A - Mohapatra, Debendra K.; Chaudhuri, Siddhartha Ray; Sahoo, Gokarneswar; Gurjar, Mukund K. (Tetrahedron-Asymmetry, 2006)
A carbohydrate based approach for the enantioselective synthesis of the polyketide acid unit present in nagahamide A has been reported. Reductive ring opening of a chiral cyclopropane ketone group to enantioselectively install the methyl and propyl groups, is a salient feature of this synthesis. (c) 2006 Elsevier Ltd. All rights reserved.

Synthesis of the spiro fused beta-lactone-gamma-lactam segment of oxazolomycin - Mohapatra, Debendra K.; Mondal, Dhananjoy; Gonnade, Rajesh G.; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
An effective synthetic strategy for construction of the novel spiro-bicyclic beta-lactone-gamma-lactam system present in oxazolomycin has been demonstrated. The 3,4-disubstituted pyrrolidine ring system was constructed via an Evans aldol reaction. The spiro-beta-lactone ring was elaborated from a gem-hydroxymethyl moiety that was successfully installed by an aldol followed by a crossed Cannizzaro reaction. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: crossed Cannizzaro reaction; Evans' aldol reaction; Garner's aldehyde; intramolecular Mitsunobu reaction; ruthenium tetroxide oxidation

Short and efficient synthetic strategy for the total syntheses of (S)-(+)- and (R)-(-)-Plakolide A - Mohapatra, Debendra K.; Pramanik, Chintnoy; Chorghade, Mukund S.; Gurjar, Mukund K. (European Journal of Organic Chemistry, 2007)
Concise and efficient total syntheses of anticancer agents (S)(+)-Plakolide A and (R)-(-)-Plakolide A were accomplished in eight steps and an overall yield of 39 % starting from geraniol. The key steps in our strategy are Sharpless asymmetric epoxidation, double elimination, and Stille coupling reactions.
Keywords: Cross-coupling; epoxidation; inhibitors; olefination

Syntheis of unusual tricyclic ring systems of biological interest - Mohapatra, Debendra K.; Maity, Pradip K.; Chorghade, Mukund S.; Gurjar, Mukund K. (Heterocycles, 2007)
We describe a new synthesis of tricyclic scaffolds that incorporate a fusion of triazole with 1,4-benzodiazepine utilizing intramolecular ``click'' chemistry.
Keywords: 1; 2; 3-Triazole; 4-benzodiazepine; Click chemistry; nitrogen rich polycyclic hetero-system; privileged structure

Synthesis of the C19-C34 segment of amphidinolide C - Mohapatra, Debendra K.; Rahaman, Hasibur; Chorghade, Mukund S.; Gurjar, Mukund K. (Synlett, 2007)
The synthesis of the C19-C34 segment of amphidinolide C is described. The key steps include the Mioskowski's Lewis acid catalyzed epoxide opening with the alcohol, ring-closing metathesis, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide C; Cytotoxic; Nozaki-Hiyama-Kishi coupling; Ring-closing metathesis; Wittig reaction

Stereoselective synthesis of the C33-C44 fragment of palau'amide - Mohapatra, Debendra K.; Nayak, Sabita (Tetrahedron Letters, 2008)
An efficient stereoselective synthesis of the C33-C44 fragment of palau'amide is described using a Sharpless asymmetric epoxidation, a regioselective nucleophilic ring opening of the epoxide, a Grignard reaction and a Luche stereoselective reduction of a keto compound as the key steps. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Cytotoxic; Luche's stereoselective reduction; palau'amide; Sharpless asymmetric epoxidation; Stereoselective

Synthesis of the C14-C29 segment of amphidinolide U utilizing a tandem dihydroxylation-S(N)2 cyclization protocol - Mohapatra, Debendra K.; Rahaman, Hasibur (Synlett, 2008)
The synthesis of the C14-C29 subunit of amphidinolide U is described. The key steps include the trans-2,5-disubstituted tetrahydrofurans via a highly diastereoselective and high yielding tandem dihydroxylation-S(N)2 cyclization, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide U; Cytotoxic; Nozaki-Hiyama-Kishi coupling; tandem dihydroxylation-S(N)2 cyclization; Wittig reaction

Stereoselective synthesis of the densely functionalized C1-C9 fragment of amphidinolides C and F - Mohapatra, Debendra K.; Dasari, Pavankumar; Rahaman, Hasibur; Pal, Rita (Tetrahedron Letters, 2009)
The synthesis of the C1-C9 subunit of amphidinolides C and F is described. Key steps include tandem Sharpless asymmetric dihydroxylation-S(N)2 cyclization reaction, Lewis acid-mediated epoxide opening, Wittig reaction, and Wacker oxidation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amphidinolide C and F; Cytotoxic; Tandem dihydroxylation-S(N)2; Wacker oxidation; Wittig reaction

Syntheis of new chiral 5,6,7,8-tetrahydrotetrazolo[1,5-a]pyrazines from alpha-amino acid derivatives following ``click'' chemistry - Mohapatra, Debendra K.; Maity, Pradip K.; Ghorpade, Ravindra V.; Gurjar, Mukund K. (Heterocycles, 2009)
An efficient and practical synthesis of new chiral fused tetrazoles have been synthesized following [3+2] cycloaddition reaction starting from alpha-amino acid derivatives.
Keywords: Amino acid; Click chemistry; Hypertension; Nitrogen Rich System; Tetrazole

Stereoselective formal total synthesis of novel antibiotic (-)-centrolobine - Mohapatra, Debendra K.; Pal, Rita; Rahaman, Hasibur; Gurjar, Mukund K. (Heterocycles, 2010)
A concise and stereoselective formal total synthesis of (-)-centrolobine is achieved utilizing Mioskowski's Lewis acid mediated epoxide opening followed by ring-closing metathesis as the key reaction.
Keywords: antibiotic; Centrolobine; Keck allylation; Ring-closing metathesis; Sharpless asymmetric epoxidation

Synthetic studies of superstolide A: a carbohydrate based synthesis of the C21-C26 segment - Pal, Rita; Rahaman, Hasibur; Mohapatra, Debendra K.; Gurjar, Mukund K. (Letters in Organic Chemistry, 2010)
The synthesis of C21-C26 fragment of superstolide A, starting from D-glucose diacetonide, involving regioselective ring opening of epoxide by Grignard reagent and regioselective stereospecefic hydroboration oxidation has been described.
Keywords: Chiral pool; Potent cytotoxic; Regioselective epoxide opening; Stereoselective hydroboration-oxidation; Superstolide A